Simple Story Of A Soldier : Life And Service in the 2d Mississippi Infantry - Hankins, Samuel W. (Book collections on Project MUSE., 2004)
This fast-paced memoir was written in 1905 by 61-year-old Samuel W. Hankins while he was living in the Soldiers Home in Gulfport, Mississippi. It vividly details his years as a Confederate rifleman from the spring of 1861, when at a mere sixteen years of age he volunteered for the 2d Mississippi Infantry, through the end of the war in 1865, when he was just twenty years old and maimed for life. The 2d Mississippi was part of the Army of Northern Virginia and as such saw action at Bull Run/Manassas, Seven Pines and the Peninsular Campaign, and Gettysburg. Besides being hospitalized with measl.